Detection and analysis of Serpin and RP26 specific antibodies for monitoring Schistosoma haematobium transmission. - Mio Kokubo-Tanaka; Anna Overgaard Kildemoes; Evans Asena Chadeka; Benard Ngetich Cheruiyot; Taeko Moriyasu; Miho Sassa; Risa Nakamura; Mihoko Kikuchi; Yoshito Fujii; Claudia J de Dood; Paul L A M Corstjens; Satoshi Kaneko; et al. (PLoS Neglected Tropical Diseases)
Background Schistosoma haematobium is the causative pathogen for urogenital schistosomiasis. To achieve progress towards schistosomiasis elimination, there is a critical need for developing highly sensitive and specific tools to monitor transmission in near-elimination settings. Although antibody detection is a promising approach, it is usually unable to discriminate active infections from past ones. Moreover, crude antigens such as soluble egg antigen (SEA) show cross-reactivity with other parasitic infections, and it is difficult to formulate the standard preparations. To resolve these issues, the performances of recombinant antigens have been evaluated. The antibody responses against recombinant S. haematobium serine-protease inhibitor (ShSerpin) and RP26 were previously shown to reflect active schistosome infection in humans. Furthermore, antibody detection using multiple recombinant antigens has been reported to improve the accuracy of antibody-based assays compared to single-target assays. Therefore, we examined the performances of ShSerpin, RP26 and the mixture of these antigens for detecting S. haematobium low-intensity infection and assessed the potential for transmission monitoring. Methodology/principal findings We collected urine and plasma samples from school-aged children in Kwale, Kenya and evaluated S. haematobium prevalence by number of eggs in urine and worm-derived circulating anodic antigen (CAA) in plasma. Among 269 pupils, 50.2% were CAA-positive by the lateral flow test utilizing up-converting phosphor particles (UCP-LF CAA), while only 14.1% were egg-positive. IgG levels to S. haematobium SEA (ShSEA), ShSerpin, RP26, and the mixture of ShSerpin and RP26 were measured by ELISA. The mixture of ShSerpin and RP26 showed the highest sensitivity, 88.7%(125/141)among the four antigens in considering indecisive UCP-LF CAA results as negative. Conclusion/significance IgG detection against the ShSerpin-RP26 mixture demonstrated better sensitivity for detection of active S. haematobium infection. This recombinant antigen mixture is simpler to produce with higher reproducibility and can potentially replace ShSEA in monitoring transmission under near-elimination settings.